(untitled) (PerCursos, 2025)
Having the sociability related to men’s football played in Rio de Janeiro as the central object of analysis, I propose a reflection on the datafication process developed in this environment. It is observed that quantification in football has been expanding rapidly, whether on the field or, especially, through the datafication and quantification carried out with fans and by public bodies that operate in the security and justice of football matches. Document analysis, fieldwork with informal dialogues, and interviews were used as methodological resources. A mismatch between the production of data for public and private use was identified, in addition to the duality of data production, both for verifying the effectiveness of public policy actions in the football environment and for controlling and surveilling fans present in stadiums.